Social and solidarity economy: Is there a new economy in the making? - Peter Utting; Nadine van Dijk; Marie-Adélaïde Matheï (United Nations Research Institute for Social Development (UNRISD), 2014)
Multiple global crises and heightened concerns about the social and environmental consequences of economic growth and liberalization have reignited interest in alternative production and consumption patterns, and ways of organizing enterprise activities. In recent years, considerable attention has focused on Social and Solidarity Economy (SSE). The term is increasingly used to refer to organizations and enterprises engaged in the production and exchange of goods and services, which are autonomous from the state and are guided by objectives and norms that prioritize social well-being, cooperation and solidarity. They include, for example, cooperatives and other social enterprises, mutual associations, women's self-help groups, unions of informal economy workers, fair trade networks, and solidarity finance schemes. Are we seeing in SSE the foundations of a new economy that not only significantly reduces the scope for negative social and environmental externalities associated with conventional for-profit enterprise, but also fosters equitable patterns of resource and surplus distribution and promotes social, cultural and power relations that can be considered democratic, empowering and emancipatory? As SSE expands, the organizations and enterprises involved often become more immersed in relations with markets and state institutions. How do such relations affect SSE? What forms of collective action and participation can ensure that closer interaction with both states and markets can facilitate, rather than undermine, SSE and its core values? This paper examines these questions. It synthesizes the insights and findings of some 70 papers and think pieces prepared under the research project on Potential and Limits of Social and Solidarity Economy organized by the United Nations Research Institute for Social Development (UNRISD). Part I appraises the potential and limits of SSE as a means of addressing some of the major development challenges currently facing both people and the planet. It identifies various benefits of collective action and economic activities grounded in ethical values and active citizenship. It cautions, however, against romanticized notions of SSE that fail to examine numerous constraints and trade-offs that affect the expansion and reproduction. It goes on to identify a variety of pressures and dilemmas that confront SSE as it scales up and interacts with states and markets...
Keywords: 330